2021
DOI: 10.48550/arxiv.2102.03423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Majorana Bound States Induced by Antiferromagnetic Skyrmion Textures

Sebastián A. Díaz,
Jelena Klinovaja,
Daniel Loss
et al.

Abstract: Majorana bound states are zero-energy states predicted to emerge in topological superconductors and intense efforts seeking a definitive proof of their observation are still ongoing. A standard route to realize them involves antagonistic orders: a superconductor in proximity to a ferromagnet. Here we show this issue can be resolved using antiferromagnetic rather than ferromagnetic order. We propose to use a chain of antiferromagnetic skyrmions, in an otherwise collinear antiferromagnet, coupled to a bulk conve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Our braiding protocol in MZM racetracks relies on the MZM track exchange, which is a process that allows pairs of MZMs to simultaneously swap track. In contrast to prior works which have discussed the spatial exchange of a MZM pair by means of T-junctions [81], Yjunctions [111], or skyrmion-based racetracks [112], here the braiding transformation stems solely from the MZM track exchange. As we show in this work, additional processes which shuttle the MZMs in the racetrack in order to complete the MZM exchange, do not contribute to the non-Abelian part of the Berry phase picked up by the twofold-degenerate ground state of the system.…”
Section: Discussionmentioning
confidence: 96%
“…Our braiding protocol in MZM racetracks relies on the MZM track exchange, which is a process that allows pairs of MZMs to simultaneously swap track. In contrast to prior works which have discussed the spatial exchange of a MZM pair by means of T-junctions [81], Yjunctions [111], or skyrmion-based racetracks [112], here the braiding transformation stems solely from the MZM track exchange. As we show in this work, additional processes which shuttle the MZMs in the racetrack in order to complete the MZM exchange, do not contribute to the non-Abelian part of the Berry phase picked up by the twofold-degenerate ground state of the system.…”
Section: Discussionmentioning
confidence: 96%
“…We note that even more complicated non-collinear magnetic textures, such as skyrmions or skyrmion chains, were proposed as an alternative route to generate topological superconducting phases. [157][158][159][160][161][162][163][164][165][166][167] Alternatively, we note that external driving provides a powerful tool to turn initially nontopological materials into topological ones. 128,129 Indeed, it has been shown that a time-dependent magnetic or electric field can give rise to Floquet Majorana fermions.…”
Section: Alternative Realizations Of Majorana Bound States In 1d Systemsmentioning
confidence: 89%
“…Another way to create superconductor / noncollinear magnet bilayers hosting magnetic excitations with a large topological index Q is to consider skyrmion lattices, ribbons or chains with the proximity-induced superconductivity, Refs. [36,174]. In Ref.…”
Section: Topological Superconductivity In the Skyrmion Chain And Latticementioning
confidence: 99%
“…skyrmion chains, were considered in Ref. [174]. To avoid the problem of the suppression of superconductivity by ferromagnetic correlations, an antiferromagnetic skyrmion chain (ASC) was considered, see Fig.…”
Section: Topological Superconductivity In the Skyrmion Chain And Latticementioning
confidence: 99%